Empowering Rural Women Through Aromatherapy Soap Production using Local Essential Oils in Indonesia - Nizori, Addion; Tafzi, Fitry; Mursalin, Mursalin; Hasnah, Nur; Nurfaijah, Nurfaijah (LPPM Universitas Jambi, 2023)
This community engagement program aimed to empower rural women from the PKK group in Mendalo Darat Village, Indonesia, through training in aromatherapy soap production using locally sourced citronella essential oil. The program involved socialization sessions, hands-on training, and mentoring to enhance participants’ knowledge and practical skills. Participants were actively engaged in the entire soap-making process, including formulation, mixing, molding, and packaging. The training improved participants’ technical competencies and increased their interest in home-based entrepreneurship. Additionally, participants were introduced to the use of digital media for product promotion, marking a significant step toward digital literacy and market access. While the program successfully boosted initial skills and confidence, it also revealed a need for further training in business management and sustainable marketing practices. This initiative demonstrates the potential of combining local resources with skill-building to support women's economic empowerment in rural settings. Future programs should include entrepreneurship development and SME partnerships to strengthen long-term sustainability and impact.